Pagan Gods as Figures of Speech: Dante's Use of Servius in the Vita Nova. (3rd July 2021) - Vitale, Vincenzo
ABSTRACT: The article sets out to show the ideological significance of the quotations from Vergil, Lucan, Horace, Homer, and Ovid found in Vita Nova 16 [XXV], the celebrated passage where Dante cites these poets as examples of personification in classical literature. In the quotations from Vergil's Aeneid, Aeolus and Juno speak to each other, and Apollo speaks to the Trojans. In his framing of the quotations, Dante appears implicitly to regard pagan deities like Aeolus, Juno, and Apollo as inanimate things, raising the question as to why the author of the Vita Nova understood pagan gods in terms of poetic tropes. Focusing on the Vergilian quotations, this essay argues that Servius's commentary to the Aeneid represents one of the major sources that might have led Dante to construe pagan deities as rhetorical personifications.